Endocytosis and Signaling (Progress in Molecular and Subcellular Biology,, 2018)
This book focuses on the context dependency of cell signaling by showing how the endosomal system helps to structure and regulate signaling pathways. The location and concentration of signaling nodes regulate their activation cycles and engagement with distinct effector pathways. Whilst many cell signaling pathways are initiated from the cell surface, endocytosis provides an opportunity for modulating signaling networks' output. In this book, first a series of reviews describe the endocytic and endosomal system and show how these subcellular platforms sort and regulate a wide range of signaling pathway components and phenotypic outputs. The book then reviews the latest scientific insights into how endocytic trafficking and subcellular location modulate a set of major pathways that are essential to normal cellular function and organisms' development. .